Highly efficient silver particle layers on glass substrate synthesized by the sonochemical method for surface enhanced Raman spectroscopy purposes - Suchomel, Petr; Prucek, Robert; Černá, Klára; Fargašová, Ariana; Panáček, Aleš; Gedanken, Aharon; Zbořil, Radek; Kvítek, Libor (Ultrasonics sonochemistry, 2016)
A fast method for preparing of silver particle layers on glass substrates with high application potential for using in surface enhanced Raman spectroscopy (SERS) is introduced. Silver particle layers deposited on glass cover slips were generated in one-step process by reduction of silver nitrate using several reducing agents (ethylene glycol, glycerol, maltose, lactose and glucose) under ultrasonic irradiation. This technique allows the formation of homogeneous layers of silver particles with sizes from 80nm up to several hundred nanometers depending on the nature of the used reducing agent. Additionally, the presented method is not susceptible to impurities on the substrate surface and it does not need any additives to capture or stabilize the silver particles on the glass surface. The characteristics of prepared silver layers on glass substrate by the above mentioned sonochemical approach was compared with chemically prepared ones. The prepared layers were tested as substrates for SERS using adenine as a model analyte. The factor of Raman signal enhancement reached up to 5·10(5). On the contrary, the chemically prepared silver layers does not exhibit almost any pronounced Raman signal enhancement. Presented sonochemical approach for preparation of silver particle layers is fast, simple, robust, and is better suited for reproducible fabrication functional SERS substrates than chemical one.
Keywords: Surface enhanced Raman spectroscopy; Glass substrate; Sonochemical; Silver particles layer